PENGARUH EMPLOYEE COMPENSATION PADA EMPLOYEE PERFORMANCE DI HOSPITALITY INDUSTRY - Pratomo, Aditya (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p17, 2022)
This research aims to analyse the effect of compensation on employee performance at hospitality Industry. The quantitative method is used to collect the data for this research. The data were collected by using questionnaires and were strengthened by the interview process, presenting the data, and drawing conclusions from the research. Sampling techniques for this study were using purposive sampling, with simple linier regression used to analysed the data. The result of this research shows that compensation given by the company to their employee has a positive with a medium impact and significant on the staff’s performance to work in the hotel.